Ecology and physiology of Eleusine indica seeds - Chin, H. F.; Raja Harun, Raja Muhammad (1979)
The ecology, morphology, production and physiology of Eleusine indica seeds were studied. Emphasis was on germination, as it determined success or failure as a competitor in a crop. E. indica seeds germinated best without glumes, at alternating temperatures of 20/35 deg C in light. Soaking seeds prior to incubation resulted in higher germination percentage. There are no natural inhibitors present in the seeds or spikelets to prevent germination. Seeds were soaked in 10-10 000 p.p.m. 2,2-DPA [dalapon], MSMA, paraquat and simazine before germination. Paraquat effectively inhibited germination even at 100 p.p.m.